Rare KCNJ18 variants do not explain hypokalaemic periodic paralysis in 263 unrelated patients. Issue 1 (16th April 2015) - Kuhn, Marius; Jurkat-Rott, Karin; Lehmann-Horn, Frank
Abstract : Objective: To examine rare KCNJ18 variations recently reported to cause sporadic and thyrotoxic hypokalaemic periodic paralysis (TPP). Methods: We sequenced KCNJ18 in 474 controls (400 Caucasians, 74 male Asians) and 263 unrelated patients with periodic paralysis (PP), including 30 patients with TPP without mutations in established PP genes. Results: In 10 patients without TPP, we identified 9 heterozygous, novel variations (c.–3G>A, L15S, R81C, E273X, T309I, I340T, N365S, G394R, R401W) and a questionable heterozygous causative R399X stop variant. Studies on 40 relatives of these 10 patients showed that none of the variants were de novo in the patients and that R399X occurred in 3 non-affected relatives. Most affected amino acids lacked conservation and several clinically affected relatives did not carry the patient's variant. T309I, however, could be pathogenic under the pre-requisite of strongly reduced penetrance in females. Of the controls, 17 revealed 12 novel rare variants including the heterozygous E273X stop variant in three individuals. Conclusions: Our study shows many different, rare KCNJ18 alterations in patients as well as controls. Only perhaps one meets the requirements of a disease-causing mutation. Therefore, KCNJ18 alterations are seldom pathogenic. Additional studies are required before patients with PP can be genetically diagnosed on the basis of a KCNJ18 variant alone.